1967
DOI: 10.1002/cne.901300304
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the number of myelin lamellae and axon circumference in fibers of vagus and sciatic nerves of mice

Abstract: Nerve fiber populations of the vagus and sciatic nerves of mice were classified according to the number of myelin lamellae present in the sheaths. This method for classifying fiber populations was superior to others used previously since it provided a more sensitive procedure for the analysis of individual fibers and better control over the technical factors involved in tissue processing.The relationship of the number of myelin lamellae in the sheath to axon circumference was found to be linear. In fresh tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
1
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(71 citation statements)
references
References 21 publications
10
59
1
1
Order By: Relevance
“…But if cats 1, 3 and 4 are taken as typical, and cat 2 as having unusually thin myelin sheaths, then it may be concluded that g is about 0 70 for group III and small y fibres, falls to about 0-62 for group II and large y fibres and then rises again to 0-72 for group I and a fibres ( Fig. 10 and Table 2 Axon perimeter and number of myelin lamellae are linearly related for all sizes of axon in peripheral nerves in the mouse and rat (Friede & Samorajski, 1967, 1968, in rat ventral spinal roots (Fraher, 1972) and in central tracts in rat and cat (Samorajski & Friede, 1969;Bishop, Clare & Landau, 1971). There are few axons larger than 20 ,tm in perimeter in most mice and rats.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…But if cats 1, 3 and 4 are taken as typical, and cat 2 as having unusually thin myelin sheaths, then it may be concluded that g is about 0 70 for group III and small y fibres, falls to about 0-62 for group II and large y fibres and then rises again to 0-72 for group I and a fibres ( Fig. 10 and Table 2 Axon perimeter and number of myelin lamellae are linearly related for all sizes of axon in peripheral nerves in the mouse and rat (Friede & Samorajski, 1967, 1968, in rat ventral spinal roots (Fraher, 1972) and in central tracts in rat and cat (Samorajski & Friede, 1969;Bishop, Clare & Landau, 1971). There are few axons larger than 20 ,tm in perimeter in most mice and rats.…”
Section: Resultsmentioning
confidence: 96%
“…A. BOYD AND K. U. KALU subdivision of fibres into groups. The number of myelin lamellae, however, is almost constant along an internode, and Friede & Samorajski (1967) suggested that it was a better criterion to employ. This has been done throughought this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Another relevant aspect of axonal development is the determination of axonal caliber, which is influenced by intrinsic neuronal factors and extrinsic factors related to myelination (Friede and Samorajski, 1967). In fact, glial cells sense axonal diameter and from this information they determine whether an axon should be myelinated and the size of myelin sheath to synthesize.…”
Section: Mitochondria and Axonal Maturationmentioning
confidence: 99%
“…In spite of the great utilization of morphometric techniques in neuropathy studies, this technique has proven extremely useful for the definition of normal parameters of nerves, either in humans (O'Sullivan & Swallow, 1968;Ochoa, 1971;Jacobs & Love, 1985) or in laboratory animals (Friede & Samorajski, 1967;Sato et al, 2006;Schiavoni & Fazan, 2006). Thus, data obtained with morphometry is used as the morphological basis for investigation of systemic and/or local diseases that compromise the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%